Improvement of infection control management by routine molecular evaluation of pathogen clusters - Mutters, Nico T.; Heeg, Klaus; Späth, Isabel; Henny, Nicole; Günther, Frank (Diagnostic microbiology and infectious disease, 2017)
Background: Undetected pathogen clusters can often be a source of spreading in-hospital infections. Unfortunately, detection of clusters can be problematic because epidemiological connection is not always easily established. Infection prevention and control (IPC) measures, however, are most effective when applied at the earliest possible stage. Aim: The goal of our study was to evaluate the benefits of routine use of molecular typing techniques for IPC management in a large University teaching hospital. Methods: We implemented daily routine molecular typing of pathogen clusters using cost-effective standard methods such as random amplified polymorphic DNA PCR, multiple-locus variable number tandem repeat analysis, and spa-typing over a 4-year study period (2012-2015). Findings: Four pathogen clusters were evaluated: (I) 14 cases of Clostridium difficile in a peripheral ward, (II) 17 cases of methicillin-resistant Staphylococcus aureus (MRSA) in two intensive-care units (ICUs), (III) 21 cases of multidrug-resistant Klebsiella pneumoniae within one department, and (IV) 6 cases of vancomycin-resistant Enterococcus faecium in an interdisciplinary ICU. Typing revealed that cluster I was not caused by an outbreak strain but was likely due to different endogenous infections. Clusters III and IV showed a classical space-time clustering of point source outbreaks. Cluster II represented a prolonged temporal cluster, which would have gone undetected without molecular typing because of large intercase intervals. Conclusion: Implementing daily routine molecular typing is effective for detecting and analyzing pathogen clusters. Falsely suspected outbreaks can be quickly resolved, whereas actual outbreaks can be identified faster, so that targeted IPC measures can be applied earlier.